The contribution of stretch-shortening cycle and arm-swing to vertical jumping performance in children, adolescents, and adult basketball players - Gerodimos, V.; Zafeiridis, A.; Perkos, S.; Dipla, K.; Manou, V.; Kellis, S. (Pediatric Exercise Science, 2008)
This study examined from childhood to adulthood: (1) the effects of countermovement (use of stretch-shortening cycle-SSC) and arm-swing (AS) on vertical jumping (VJ) performance and (2) the ability to use the SSC and AS during VJ. Male basketball players (n = 106) were divided according to their age into: children (12.0 ± 0.23), young adolescents (14.5 ± 0.41), old adolescents (16.9 ± 0.27), and adults (21.9 ± 0.32). Each participant executed three maximal squat jumps (SJ), countermovement jumps without arms (CMJ) and with arms (CMJA). The contribution of SSC and AS was calculated by the augmentation (difference and percent change) in performance between CMJ and SJ, and CMJA and CMJ, respectively. CMJA performance was significantly (p < .05) higher than CMJ and SJ, and CMJ was higher than SJ within all age-groups. There were no significant differences (p > .05) among children, young and old adolescents, and adults in the percent contribution of SSC and AS to VJ performance. The variability in the contribution of SSC and AS to VJ performance was about twofold higher in children vs. adults. It appears that the ability to use the SSC and AS is not affected by the maturation process in males, trained in basketball.